2022
DOI: 10.1007/s10811-022-02734-x
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-induced chemical, mechanical, and behavioral changes in marine microalgae

Abstract: This study examines how salinity reduction triggers the response of three marine microalgae at the molecular and unicellular levels in terms of chemical, mechanical, and behavioral changes. At the lowest salinity, all microalgal species exhibited an increase in membrane sterols and behaved stiffer. The glycocalyx-coated species Dunaliella tertiolecta was surrounded by a thick actin layer and showed the highest physiological activity, negatively affecting cell motility and indicating the formation of the palmel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Another important property of the cell surface that may change, depending on growth conditions, is the rigidity of the cell wall. Indeed, several studies have shown that a specific stress or a change in environmental conditions (such as a change in pH, temperature, or salinity) can have an important effect on the composition or remodeling of the cell wall, thereby changing its nanomechanical properties [60][61][62][63][64][65][66]. Our nanoindentation measurements, performed on C. closterium cells exposed to nanoplastics, showed a significant decrease in cell wall rigidity compared to cells grown without nanoplastics (Figure 7).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Another important property of the cell surface that may change, depending on growth conditions, is the rigidity of the cell wall. Indeed, several studies have shown that a specific stress or a change in environmental conditions (such as a change in pH, temperature, or salinity) can have an important effect on the composition or remodeling of the cell wall, thereby changing its nanomechanical properties [60][61][62][63][64][65][66]. Our nanoindentation measurements, performed on C. closterium cells exposed to nanoplastics, showed a significant decrease in cell wall rigidity compared to cells grown without nanoplastics (Figure 7).…”
Section: Discussionmentioning
confidence: 68%
“…A change in the Young modulus of cells was also observed when the pH of the culture medium changed, and it increased significantly at a higher pH [61]. In addition, previous studies by our group [64,65,68] have shown that the exposure of cells to temperature stress, salinity stress, and cadmium causes changes in cell rigidity, as a consequence of a molecular modification to the cell barrier. It is therefore not surprising that exposure to nanoplastics also alters the nanomechanical properties of cells.…”
Section: Discussionmentioning
confidence: 70%
“…Glycocalyx acts as an intermediate and protects cell membrane against direct physical forces and environmental stresses allowing it to maintain its integrity. The attachment of cell membrane to cell cover takes place by membrane proteins (74)(75). D. salina alga which lives in hypersaline environments, adjusts itself to these ecosystems by cell plasma membrane protein kinases and also by internal glycerol synthesis which help cells to make osmotic adjustment to high external saline conditions (76).…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae have different tolerance levels for salinity. Changes in salinity can affect the production of antioxidants in marine and halotolerant microalgae [34].…”
Section: Factors Influencing Antioxidant Production In Microalgaementioning
confidence: 99%